BRAZILIAN KEY–THINKERS ON EDUCATION - FERREIRA, IVAN VILELA; WIGGERS, INGRID DITTRICH (Society Register, 2018)
It is almost a consensus among the Brazilians that, in order to solve the social issues, the education must be improved. Thus, the present study aimed to analyze the Brazilian key-thinkers on education. Rui Barbosa, Fernando de Azevedo, Anísio Teixeira, Cecília Meireles, and Paulo Freire were selected because they worked to develop some aspects of education: politics, educational system, philosophy of education, childhood education and pedagogical methods. These intellectuals fought against powerful societal forces, but they did not give up on transforming the Brazilian education, and, consequently, the Brazilian society. Therefore, they were selected to represent the Brazilian key-thinkers on education.